A REVIEW OF MENTAL HEALTH POLICY AND IMPLEMENTATION IN GHANA: A ROADMAP TO ACHIEVING SUSTAINABLE DEVELOPMENT GOAL (SDG) 3 - Magna, E. K.; Yemoh, T. A. (UDS International Journal of Development, 2018)
The paper is a review of works on mental health in Ghana which identified some barriers to mental health policy implementation tomeeting the Sustainable Development Goal 3 (SDG 3) by 2030. A total of 31/42 articles were reviewed and included in the study. Barriers to the effective implementation of mental health policy identified by reviewers included the low priority of mental health, inadequate human resources, lack of consultation in policy formulation, ineffective policy dissemination, and the absence of an evidence base for policy directives. Other barriers included insufficient funding for mental health services; mental health resources centralized in and near big cities and in large institutions; complexities of integrating mental health effectively in primary care; low numbers and limited types of health workers trained and supervised in mental health care, and mental health leaders often deficient in public health skills and experience. It was suggested that the much-anticipated passing of the Mental Health Bill in Ghana will provide the impetus for the development of new mental health policy. New concepts for a revised policy must include a rights-based perspective and promote best practices in mental health, in line with the proposed legislation. However, it is essential that any new mental health policy does not follow the path of previous policies by providing both the financing and resources for its successful implementation, and ensuring that all stakeholders including users, careers, health workers and other sectors such as social welfare and the police, are consulted throughout the policy development process. In addition, it is important that those responsible for implementation at the frontline of health service delivery are provided with the necessary training and resources to implement the policy. Keywords: Sustainable Development Goals, Alcohol, Mental, Psychiatric, Policy